Porous COS@SiO2 Nanocomposites Ameliorate Severe Acute Pancreatitis and Associated Lung Injury by Regulating the Nrf2 Signaling Pathway in Mice - Mei, Qixiang; Deng, Guoying; Huang, Zehua; Yin, Yue; Li, Chunlin; Hu, Junhui; Fu, Yang; Wang, Xingpeng; Zeng, Yue (Frontiers in Chemistry, 2020)
Severe Acute pancreatitis(SAP) is associated with high rates of mortality and morbidity. Chitosan oligosaccharides(COS) are an agent with antioxidant properties. We developed porous COS@SiO2 nanocomposites to study the protective effects and mechanisms of COS nanomedicine for the treatment of AP. Porous COS@SiO2 nanocomposites could release COS slowly in the way of pH control, so as to achieve the purpose of sustained release and keep the drug at a higher concentration. This study aimed to determine whether porous COS@SiO2 nanocomposites(COS@SiO2) ameliorate severe acute pancreatitis and associated lung injury. The SAP model was established on male C57BL/6 mice by intraperitoneal injection of caerulein. Expression levels of MPO, MDA, SOD, NF-κB, NLRP3 inflammasome, Nrf2 and inflammatory cytokines were detected, and a histological analysis of mice pancreas and lung tissues was performed. In SAP groups, systemic inflammation and oxidative stress occur, and pathological damages to the pancreas and lung were obvious. Combined with porous COS@SiO2 nanocomposites pretreatment, systemic inflammatory response were obviously reduced, as well as oxidative stress indicators in targeted tissues.It was found that Nrf2 was significantly activated in the COS@SiO2 treatment group, and the expression of NF-κB and NLRP3 inflammasome was notably decreased. What’s more, this protection effect was significantly weakened when Nrf2 signaling was inhibited by ML385. We suppose that porous COS@SiO2 nanocomposites activate Nrf2 signaling pathway to inhibit oxidative stress and reduce the produce of NF-κB and NLRP3 inflammasome and the release of inflammatory factors, thus block the systemic inflammatory response, and ultimately ameliorate severe acute pancreatitis and associated lung injury.